2022
DOI: 10.1088/1741-4326/ac47b4
|View full text |Cite
|
Sign up to set email alerts
|

Overview of JET results for optimising ITER operation

Abstract: The JET 2019-2020 scientific and technological programme exploited the results of years of concerted scientific and engineering work, including the ITER-like wall (ILW: Be wall and W divertor) installed in 2010, improved diagnostic capabilities now fully available, a major Neutral Beam Injection (NBI) upgrade providing record power in 2019-2020, and tested the technical & procedural preparation for safe operation with tritium. Research along three complementary axes yielded a wealth of new results. Firstly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 150 publications
0
79
0
Order By: Relevance
“…The pulses considered are JET pulses 42464 and 42982. Both plasmas have I p = 3.8 MA, B T = 3.8 T, a C plasma facing wall (and, consequently a different impurity mix with respect to the references modelled in the previous section) and use a 3 He minority ICRH heating scheme (as opposed to the H minority scheme used in the shots described in the previous section). Shot 42464 is a pure D plasma, whereas shot 42982 is a 50-50 DT plasma.…”
Section: Modelling Dte1 Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…The pulses considered are JET pulses 42464 and 42982. Both plasmas have I p = 3.8 MA, B T = 3.8 T, a C plasma facing wall (and, consequently a different impurity mix with respect to the references modelled in the previous section) and use a 3 He minority ICRH heating scheme (as opposed to the H minority scheme used in the shots described in the previous section). Shot 42464 is a pure D plasma, whereas shot 42982 is a 50-50 DT plasma.…”
Section: Modelling Dte1 Plasmasmentioning
confidence: 99%
“…The same modelling procedure described in the previous section is applied and the comparison between experiment and simulation results are shown in figures 10 and 11 for shot 42464 and figures 12 and 13 for shot 42982. Note that in these simulations we assumed a nominal 3 He concentration of ≈5%, considered C as the only other impurity contributing to Z eff in the plasma and adjusted its concentration to match the experimental Z eff value (inferred from Bremsstrahlung measurements). This resulted in n C / n e ≈ 3.9% for shot 42464 and n C / n e ≈ 5.6% for shot 42982.…”
Section: Modelling Dte1 Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases the performance was found to drop substantially (primarily due to changes in the pedestal from the enforced operating regime to avoid melting divertor components)-this was unpredicted and not addressed in scalings (which do not include edge atomic physics and neutral penetration effects). However, intense experimental and model-based optimisation over a number of years has recovered reliable high performance on AUG [33,34], and removed the deficit and indeed exceeded the carbonwall performance in JET [35]. As with many plasma optimisations, it is also found that the time sequence within the discharge is critical, i.e.…”
Section: Overall Plasma Parametersmentioning
confidence: 99%
“…injected into the plasma) with the best results achieved in the Joint European Tokamak (JET) [79]. The larger device International Thermonuclear Experimental Reactor (ITER) [80] aims at a tenfold increase (Q = 10), but the device, though expected to validate some key concepts needed for commercial viability, is experimental and does not attempt to generate electricity.…”
Section: Introductionmentioning
confidence: 99%